Spatial modeling for the potential location of a rubber processing factory in East Ogan Komering Ulu (OKU) Regency, South Sumatra Province - Nyokro Mukti Wijaya; Lili Somantri; Iwan Setiawan (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2022)
This study uses spatial modeling to determine the potential location of a rubber processing factory in East Ogan Komering Ulu (OKU), South Sumatra, Indonesia. This descriptive study used the map overlay method. Besides, this study also used six parameters, namely number of population, rubber plantation area, land slope, land suitability, river flow availability, and road network availability. Those six parameters were overlaid and scored to generate a map of the potential location for the rubber processing factory in East OKU, South Sumatra, Indonesia. Our analysis results suggest that the most potential location was 27.412 ha (9 percent), while the area with medium and low potential was 267.952 ha (86 percent) and 15.155 ha (5 percent), respectively. Generally, the pattern of the most potential area followed the road network pattern and river network in East OKU because both road and river facilitate the provision of water resources, as well as distribution of raw materials and produced products. These results can be used as a reference for the government of East OKU Regency in constructing the factory. Besides, this study can also be used as a Geography learning material in the course of map and mapping, as well as Geography Information System.